ӨВӨРМӨЦ ХЭЛЦ НЬ ЗҮЙРЛЭЛ (metaphor) БА ТӨЛӨӨЛӨЛ (metonym) БОЛОХ НЬ - Э.Тогтуун (Acta Mongolica, 2010)
Through this article, we attempted to explain some phrases using the word ‘Ama’ in Japanese and Mongolian in comparative and cognitive linguistics. Researching phrases through traditional linguistic and semantic approaches, that is to say, isolating them from the relation from others, cannot entirely reveal their real nature. As a result, we have faced the regular demand of research while evaluating the phrases under the cognitive linguistic definition of ‘metaphor’ and ‘metonym’.